The influence of mechanical error compensator on the quality of thin-sheet separating stamping - Мірзак, Володимир Якович; Боков, Віктор Михайлович (Eastern-European Journal of Enterprise Technologies, 2015)
The quality of the thin-sheet separating stamping depends on the state of the "press-stamp" system, namely the state of the press (rigidity and geometric accuracy) and the deformation degree of the guide assemblies in the stamp and stamping unit plates as a result of the action of technological effort. To reduce the impact of these deformations, different approaches are used: from increasing the rigidity of the unit by the number of guide assemblies and plate thickness to applying compensating devices for unloading the unit from the action of transverse forces and torques. Known compensating devices only partially solve the problem, which is not enough for the conditions of the thin-sheet separating stamping. According to the authors, the deformation of the units can be substantially reduced using the mechanical error compensator of the "press-stamp" system, mounted on the press table instead of the bolster plate, which should positively affect the quality of thin-sheet stamped parts. In the paper, the effect of mechanical compensator on the stress-strain state of the stamping unit elements and the quality of the thin-sheet separating stamping of the rotor plates was examined through a comparative analysis. It was found that using the compensator substantially reduces the deformation of the bottom plate of the stamping unit, which leads to more favorable operating conditions of the stamp guide assemblies. The rotation angle of columns, as a result of deformation of the unit plates, has decreased several times. The mechanism of the effect of the compensator on the stamping quality indices was determined. Measuring variations in the sizes of the rotor plates showed that during stamping with compensator, the deviation is 2.25 - 2.40 times lower than without it, and the distribution density of sizes during stamping with compensator is 30 - 40% higher. Thus, the research shows the feasibility of using the proposed mechanical error compensator of the "press-stamp" system to enhance the quality of the thin-sheet separating stamping, especially in large scale and mass production of parts such as core plates.